Three-dimensional superimposition for patients with facial palsy: an innovative method for assessing the success of facial reanimation procedures. Issue 1 (January 2018) - Sforza, C.; Ulaj, E.; Gibelli, D.M.; Allevi, F.; Pucciarelli, V.; Tarabbia, F.; Ciprandi, D.; Dell'Aversana Orabona, G.; Dolci, C.; Biglioli, F.
Abstract: Facial palsy is a severe condition that may be ameliorated by facial reanimation, but there is no consensus about how to judge its success. In this study we aimed to test a new method for assessing facial movements based on 3-dimensional analysis of the facial surfaces. Eleven patients aged between 42 and 77 years who had recently been affected by facial palsy (onset between 6 and 18 months) were treated by an operation based on triple innervation: the masseteric to temporofacial nerve branch, 30% of the hypoglossal fibres to the cervicofacial nerve branch, and the contralateral facial nerve through two cross-face sural nerve grafts. Each patient had five stereophotogrammetric scans: at rest, smiling on the healthy side (facial stimulus), biting (masseteric stimulus), moving the tongue (hypoglossal stimulus), and corner-of-the-mouth smile (Mona Lisa). Each scan was superimposed onto the facial model of the "rest" position, and the point-to-point root mean square (RMS) value was automatically calculated on both the paralysed and the healthy side, together with an index of asymmetry. One-way and two-way ANOVA tests, respectively, were applied to verify the significance of possible differences in the RMS and asymmetry index according to the type of stimulus (p = 0.0329) and side (p < 0.0001). RMS differed significantly according to side between the facial stimulus and the masseteric one on the paralysed side (p = 0.0316). Facial stimulus evoked the most asymmetrical movement, whereas the masseteric produced the most symmetrical expression. The method can be used for assessing facial movements after facial reanimation.